2011
DOI: 10.1038/eye.2011.31
|View full text |Cite
|
Sign up to set email alerts
|

Changes in retinal nerve fibre layer, optic nerve head morphology, and visual field after acute primary angle closure

Abstract: Aims/Purpose To determine and correlate the long-term changes in retinal nerve fibre layer (RNFL) thickness, optic nerve head (ONH) morphology, and visual fields after a single episode of acute primary angle closure (APAC). Methods This was a cross-sectional comparative study of patients at National University Hospital (Singapore) from 2000 to 2006 after an episode of unilateral APAC. The peripapillary and macular RNFL were measured using Stratus optical coherence tomography (OCT) and ONH configuration was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 25 publications
5
34
0
Order By: Relevance
“…This is in keeping with Chai et al where a reduction in rim volume was observed after a single APAC attack [13]. It is partially in keeping with the data provided by Sng CC et al where a trend of Rim Volume reduction was suggested after a single episode of APAC [21].…”
Section: Hrt Evidence Of Damagesupporting
confidence: 80%
See 1 more Smart Citation
“…This is in keeping with Chai et al where a reduction in rim volume was observed after a single APAC attack [13]. It is partially in keeping with the data provided by Sng CC et al where a trend of Rim Volume reduction was suggested after a single episode of APAC [21].…”
Section: Hrt Evidence Of Damagesupporting
confidence: 80%
“…This result is in keeping with Sng et al where peripapillary loss of RNFL was diagnosed after a single episode of APAC [21]. Furthermore, Chew et al noted that even if cup to disc ratio did not change, there was significant thinning of the RNFL on HRT analysis 12 months after APAC [22].…”
Section: Hrt Evidence Of Damagesupporting
confidence: 76%
“…Acute primary angle closure (APAC) is an ophthalmic emergency and prompt treatment is necessary to reduce the rates of vision-threatening consequences 1 2. If left untreated, persistently high intraocular pressure (IOP) can lead to synechial angle damage and glaucomatous optic neuropathy 1 3.…”
Section: Introductionmentioning
confidence: 99%
“…If left untreated, persistently high intraocular pressure (IOP) can lead to synechial angle damage and glaucomatous optic neuropathy 1 3. A long duration of raised IOP has been associated with retinal nerve fibre layer thinning,4 5 significant visual field defects6 7 and disc pallor 2. Conventional treatment of APAC involves reducing the IOP with systemic and topical medications, such as acetazolamide and β-blockers, followed by laser peripheral iridotomy to relieve the pupil block 8 9.…”
Section: Introductionmentioning
confidence: 99%
“…Even after resolution of APAC, up to 60% of eyes have persistently raised intraocular pressure (IOP) and are associated with significant visual impairment 3 4. Traditionally, eyes with narrow anterior chamber angles are at a higher risk of APAC and imaging studies have reported multiple quantifiable angle parameters associated with angle closure 5 6.…”
Section: Introductionmentioning
confidence: 99%